STEM-BASED BIOLOGY LEARNING AND ITS IMPACT ON STUDENTS LEARNING OUTCOMES - Hardiani, Santi (Universitas Tanjungpura, 2025)
Science learning, especially Biology, requires an approach that can integrate various disciplines and utilize technology to improve students' understanding and critical thinking skills. In this context, the application of Science, Technology, Engineering and Mathematics (STEM)-based learning models is a strategic step to improve learning outcomes. This research will focus on efforts to overcome various kinds of problems that are thought to be the cause of the low critical thinking of students in science subjects, to be able to create a learning atmosphere that is fun, interesting, in this study Quizizz-based learning STEM model will be carried out. The approach in this study is a quantitative approach, with the research method Experiment One Group Pretest-Post test Design model. The sample used is a saturated sample, namely all VIIIA class students as many as 42 people. The instruments used in this study were multiple choice questions on the pretest. The results of data analysis using normality test and regression and correlation analysis showed a significant effect of the application of STEM-based biology learning with increased learning outcomes.